The color red attracts attention in an emotional context. An ERP study - Kuniecki, Michał; Pilarczyk, Joanna; Wichary, Szymon (Frontiers in Human Neuroscience, 2015)
The color red is known to influence psychological functioning, having both negative (e.g., blood, fire, danger), and positive (e.g., sex, food) connotations. The aim of our study was to assess the attentional capture by red-colored images, and to explore the modulatory role of the emotional valence in this process, as postulated by Elliot and Maier's (2012) color-in-context theory. Participants completed a dot-probe task with each cue comprising two images of equal valence and arousal, one containing a prominent red object and the other an object of different coloration. Reaction times were measured, as well as the event-related lateralizations of the EEG. Modulation of the lateralized components revealed that the color red captured and later holded the attention in both positive and negative conditions, but not in a neutral condition. An overt motor response to the target stimulus was affected mainly by attention lingering over the visual field where the red cue had been flashed. However, a weak influence of the valence could still be detected in reaction times. Therefore, red seems to guide attention, specifically in emotionally-valenced circumstances, indicating that an emotional context can alter color's impact both on attention and motor behavior.